Principles of Epilepsy Management for Women in Their Reproductive Years - Spiegel, Rebecca; Merius, Heidy (Frontiers in Neurology, 2020)
In the United States, there are over one million women with epilepsy (WWE) in their childbearing years.[1] Pregnancy can be challenging for this population. A number of international registries have documented that children born to these women are at increased risk for major congenital malformations (MCM), lower intelligence quotient scores and neurodevelopmental disorders, when the mother is managed on antiseizure medications (ASMs). To prevent poor neonatal outcomes for this population, safe and thoughtful management strategies are necessary. We propose to divide these management strategies into five principles. These include (I) choosing suitable ASMs for the patient’s seizure type, (II) choosing an ASM with the least teratogenic and cognitive side effects, (III) dosing at the lowest possible effective dosage, (IV) selecting the best ASM regimen as promptly as possible, even before a woman has her first menses, and (V) supplementing these patients with folic acid to enhance cognition and reduce chances of neural tube defects in children who are exposed to ASMs in utero.